THE IMPACT OF NUTRITIONAL SCREENING ON PERITONEAL DIALYSIS USERS BY NURSES: A SYSTEMATIC REVIEW - Ridha Afzal; Syaifoel Hardy; Edison Kabak; Isak Jurun Hasan Tukayo (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2021)
Background: Continuous Ambulatory Peritoneal Dialysis (CAPD) patients deserve special attention due to metabolic changes in response to Chronic Kidney Disease (CKD) which affects their nutritional status. Assessment of nutritional status through screening carried out by Peritoneal Dialysis (PD) nurses is expected to be able to improve nutritional status and avoid complications of malnutrition. Purposes: This review and meta-analysis were carried out to determine whether there is a clinical advantage as the impact to do the nutritional screening to CAPD users. Method: The method used was critical document review of PRISMA Analysis as a systematic review through 103 document searches, identifying keywords, and reviewing articles from Google Scholar, Research Gate, and PubMed. Characteristics of the studies under the search were: nursing on CAPD users, CKD cases, nutrition assessment, roles of CAPD nurses, and nutritional screening methods. Result: Out of 103 records under the search protocol, records screened (n=64), Google Scholar: (n:36), Research Gate (n:12), PubMed (n:12), records removed (n=61), retrieved (n=41), assessed for eligibility (n-21) and records included in the study review (n=17). By using meta-analysis, 21 records were under Included of PRISMA and the studies demonstrate clinically and professionally beneficial. The study suggests Subjective Global Assessment (SGA) screening method for CAPD patients to be used by CAPD nurses.